PEMBELAJARAN PAI MENGGUNAKAN MEDIA SORT-CARD AUDIO TERHADAP SIKAP KOMUNIKATIF SISWA DI SEKOLAH DASAR: membahas hasil belajar PAI mengunakan audio sort card untuk meningkatkan kemampuan komunikasi - Nurul Malikah; Jauhan Budiwan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2020)
This study discusses the communication skills of students conveying to others in ways that need improvement. The ability of students to be able to speak and interact well is expected to stimulate cognitive abilities in Islamic Education learning. Students who are interactive communicative internalize religious behavior in everyday life. Treatment uses the Sort-Card Audio method to stimulate good communication fun. Data were analyzed by means of T test with purposive sampling conducted at Ainul Ulum Elementary School. The results showed that the difference scores of students were more communicative through the sort card method.